2020
DOI: 10.1051/e3sconf/202020212016
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Status Based on Vector Density Index and Transovarial Infection on Aedes Sp. Mosquito in Meteseh Village, Semarang City

Abstract: Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus. In 2016, the number of DHF patients in areas of Health services of Rowosari was 247 cases, IR 289.6/100.000 populations and the highest number of the patients was from Meteseh Village. The most usual mechanism happened in the vertical transmission, transovarial infection, from adult mosquito to the egg. The study was conducted to describe of entomological status of House Index (HI), Container Index (CI), Breteau Index (BI), House index (HI), O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Eradication of mosquito nests must continue to be improved to minimize water reservoirs used as breeding places for mosquitoes. Therefore, reducing the number of water reservoirs outside the home can significantly reduce mosquito population density [40], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Eradication of mosquito nests must continue to be improved to minimize water reservoirs used as breeding places for mosquitoes. Therefore, reducing the number of water reservoirs outside the home can significantly reduce mosquito population density [40], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…di suatu area tertentu. 30 Apabila suatu area menghasilkan nilai CI >5% maka area tersebut tergolong dalam kriteria risiko tinggi untuk terinfeksi DBD, sedangkan apabila area tersebut menghasilkan nilai CI <5% maka area tersebut tergolong memiliki resiko rendah untuk terinfeksi DBD. Adapun nilai CI pada penelitian ini sebesar 31% dengan nilai DF 7 atau termasuk kategori tinggi, dari hasil penelitian ini disarankan perlu adanya edukasi kepada masyarakat untuk membersihkan secara rutin TPA seperti bak mandi, drum, tempayan, memberikan bubuk abate untuk membunuh jentik yang terdapat di dalam TPA, dan menutup rapat semua TPA.…”
Section: Pembahasanunclassified
“…Similar study was found that seasonal environmental condition contributes to the ecological plasticity of male Ae. aegypti [26].…”
Section: Dispersal Pattern Of Sterile Male Ae Aegyptimentioning
confidence: 99%